1944
DOI: 10.1084/jem.79.5.463
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Lymphogranuloma Venereum

Abstract: The association of a toxin or toxic factor with a Virus has never been demonstrated although it may have been suspected. In fact, under most circumstances it is difficult to devise experiments which would demonstrate clearly the occurrence of a toxin in association with these agents since both would be of small size and usually of labile nature. Thus, ff all possible sources of confusion were controlled, a positive result would be of great value but a negative one would be without significance.For many reasons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1944
1944
2001
2001

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…The association of a toxin activity with chlamydial EBs was described 50 years ago (13), but a toxin has not been identified. Several toxin-like genes were identified in the genomes of sequenced chlamydial strains (6,7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of a toxin activity with chlamydial EBs was described 50 years ago (13), but a toxin has not been identified. Several toxin-like genes were identified in the genomes of sequenced chlamydial strains (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…A report of chlamydial toxic activity was published more than 50 years ago by Rake and Jones (13). These investigators speculated that the putative toxin was an important virulence factor in chlamydial pathogenesis.…”
mentioning
confidence: 99%
“…(TE) that is not connected with the replication Several species of Chlanlydia have been shown to produce a toxic effect on intact animals, as well as on specific tissues and cells; this effect is analogous to that produced by several species of Rickettsiae (26,33), and the factor producing the effect has been called a "toxin" (16). Many serious attempts over the years to identify a toxin have failed and the mechanism of this injurious effect remains to be established.…”
Section: Introductionmentioning
confidence: 99%
“…It has been postulated that a toxic factor may play a role in severe chlamydial diseases in man, animals, and birds (19). Rake and Jones demonstrated that some chlamydia1 strains produce a toxic effect in mice and chick embryos (25). More recently, evidence has been presented that the toxic factor is closely associated with the elementary bodies (E.B.)…”
Section: Introductionmentioning
confidence: 99%